Pengembangan LKPD Berbasis Discovery Learning Pada Mata Pelajaran IPAS Untuk Peserta Didik Kelas V SD Negeri 25 Lubuklinggau. - Arkan Naupal, Azza; Rijal, Akmal; Fitriyana, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to produce a Discovery Learning-based Student Worksheet (LKPD) that is valid, practical, and effective for Natural and Social Sciences (IPAS) instruction for Grade V students at SD Negeri 25 Lubuklinggau. The study employs the Research and Development (R&D) method using the ADDIE development model, comprising the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of three expert validators (media, language, and subject matter experts), one Grade V teacher, and Grade V students from SD Negeri 25 Lubuklinggau who participated in one-to-one, small-group, and large-group trials. Data collection techniques included observation, interviews, questionnaires, documentation, and pre-test and post-test assessments. Data analysis covered validity, practicality, and effectiveness, the latter utilizing N-Gain scores. The results indicate that the Discovery Learning-based LKPD met validity criteria, with expert assessment scores of 82% (media expert), 96% (language expert), and 96% (subject matter expert), all classified as